Synthesis and evaluation of dual fatty acid amide hydrolase-monoacylglycerol lipase inhibition and antinociceptive activities of 4-methylsulfonylaniline-derived semicarbazones - Jaiswal S.; Akhilesh; Uniyal A.; Tiwari V.; Raja Ayyannan S. (My University, 2025)
Fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL) are promising targets for neuropathic pain and other CNS disorders. Based on our previous lead compound SIH 3, we designed and synthesized a series of 4-methylsulfonylphenyl semicarbazones and evaluated for FAAH and MAGL inhibition properties. Most of the compounds showed potency towards both enzymes with leading FAAH selectivity. Compound (Z)-2-(2,6-dichlorobenzylidene)-N-(4-(methylsulfonyl)phenyl)hydrazine-1-carboxamide emerged as the lead inhibitor against both FAAH (IC50 = 11 nM) and MAGL (IC50 = 36 nM). The lead inhibitor inhibited FAAH by non-competitive mode, but showed a mixed-type inhibition against MAGL. Molecular docking study unveiled that the docked ligands bind favorably to the active sites of FAAH and MAGL. The lead inhibitor interacted with FAAH and MAGL via π–π stacking via phenyl ring and hydrogen bonding through sulfonyl oxygen atoms or amide NH. Moreover, the stability of docked complexes was rationalized by molecular simulation studies. PAMPA assay revealed that the lead compound is suitable for blood–brain penetration. The lead compound showed better cell viability in lipopolysaccharide-induced neurotoxicity assay in SH-SY5Y cell lines. Further, in-vivo experiments unveiled that dual inhibitor was safe up to 2000 mg/kg with no hepatotoxicity. The dual FAAH-MAGL inhibitor produced significant anti-nociceptive effect in the CCI model of neuropathic pain without altering locomotion activity. Lastly, the lead compound exhibited promising ex-vivo FAAH/MAGL inhibition activity at the dose of 10 mg/kg and 20 mg/kg. Thus, these findings suggest that the semicarbazone-based lead compound can be a potential template for the development of agents for neuropathic pain. © 2022 Elsevier Ltd